Abstract 4143624: The QTc Dilemma in Pediatric DKA: Which correction formula to use? - Medappa Maruvanda, Sushmitha (Circulation (New York, N.Y.), 2024)
Background: In diabetic ketoacidosis (DKA), cardiac complications such as QTc interval prolongation can pose a risk for ventricular tachycardia. The Bazett formula, a standard for QTc correction, may not be the most precise for children due to a higher heart rate variability. Hypothesis: QTc prolongation observed in pediatric DKA is the result of heart rate overcorrection by the Bazett formula. Methods: A retrospective chart review was conducted on pediatric patients admitted to Saint Peter's University Hospital Pediatric Intensive Care Unit for DKA from January 2017 to April 2024. Inclusion criteria encompassed patients under 21 years with two 12-lead ECGs taken during and after DKA resolution. QTc intervals were calculated using the Bazett, Fridericia, Hodges, Framingham, and Rautaharju formulas. Electrolyte levels and pH values were collected during and after DKA resolution. Data analysis was performed using both unpaired and paired data via Stata v18.0. Results: The study included 34 subjects, with 7 subjects having 2 DKA admissions (n=41 ECG pairs). Unpaired analysis indicated QTc prolongation using the Bazett formula in 61% of DKA cases (p=0.015), often due to heart rate overcorrection. The other formulas did not show statistically significant QTc prolongation. Paired analysis revealed a significant QTc increase during DKA compared to the resolved state (p<0.05). Additionally, changes in ionized calcium levels positively correlated with QTc changes in DKA. Conclusion: While the Bazett formula often overcorrects QTc in pediatric DKA, a true QTc interval increase does occur during DKA, albeit less significantly than previously believed. The Rautaharju formula provides a more accurate correction. The Fridericia and Hodges formulas are unreliable. An increase in ionized calcium is also noted in DKA. Current pediatric DKA management guidelines should include routine 12-lead ECGs and venous blood gas analyses with electrolytes to monitor QTc changes and mitigate arrhythmia risks.